Impact of Age and Symptom Development on SARS-CoV-2 Transmission in Households With Children—Maryland, New York, and Utah, August 2020–October 2021. (9th August 2022) - Sumner, Kelsey M; Karron, Ruth A; Stockwell, Melissa S; Dawood, Fatimah S; Stanford, Joseph B; Mellis, Alexandra; Hacker, Emily; Thind, Priyam; Castro, Maria Julia E; Harris, John Paul; Deloria Knoll, Maria; Schappell, Elizabeth; et al.
Abstract: Background: Households are common places for spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We investigated factors associated with household transmission and acquisition of SARS-CoV-2. Methods: Households with children age <18 years were enrolled into prospective, longitudinal cohorts and followed from August 2020 to August 2021 in Utah, September 2020 to August 2021 in New York City, and November 2020 to October 2021 in Maryland. Participants self-collected nasal swabs weekly and with onset of acute illness. Swabs were tested for SARS-CoV-2 using reverse transcription polymerase chain reaction. We assessed factors associated with SARS-CoV-2 acquisition using a multilevel logistic regression adjusted for household size and clustering and SARS-CoV-2 transmission using a logistic regression adjusted for household size. Results: Among 2053 people (513 households) enrolled, 180 people (8.8%; in 76 households) tested positive for SARS-CoV-2. Compared with children age <12 years, the odds of acquiring infection were lower for adults age ≥18 years (adjusted odds ratio [aOR], 0.34; 95% CI, 0.14–0.87); however, this may reflect vaccination status, which protected against SARS-CoV-2 acquisition (aOR, 0.17; 95% CI, 0.03–0.91). The odds of onward transmission were similar between symptomatic and asymptomatic primary cases (aOR, 1.00; 95% CI, 0.35–2.93) and did not differ by age (12–17 years vs <12 years: aOR, 1.08; 95% CI, 0.20–5.62; ≥18 years vs <12 years: aOR, 1.70; 95% CI, 0.52–5.83). Conclusions: Adults had lower odds of acquiring SARS-CoV-2 compared with children, but this association might be influenced by coronavirus disease 2019 (COVID-19) vaccination, which was primarily available for adults and protective against infection. In contrast, all ages, regardless of symptoms and COVID-19 vaccination, had similar odds of transmitting SARS-CoV-2. Our findings underscore the importance of SARS-CoV-2 mitigation measures for persons of all ages.